Ferroelectricity of (1-x)(Bi0.5Na0.5)TiO3 - xBa(Ti0.95Zr0.05)O3 solid solution ceramics - N. Sawangwan (2018)
(l-x)(Bi0.5Na0.5TiO3)-xBa(Ti 0.95Zr0.05)O3 ceramics were prepared by the mixed oxide technique and their dielectric, piezoelectric and ferroelectric properties determined in detail in the range x = 0.06 to 0.09. At x = 0.07 the maximum relative permittivity of 1338 and piezoelectric constant of 167 pC/N were obtained. It was concluded that 0.93(Bi0.5Na 0.5TiO3)-0.07Ba(Ti0 95Zr0.05)O 3 is the morphotropic phase boundary region for this system. © 2008 Trans Tech Publications, Switzerland.